Incidence of the use of a new English Procedure Manual before, during and after shooting duties with the AMX-13 tank of 105mm, in the teaching and learning process for the military personnel attending the specialization training course at Armored Cavalry School Riobamba during the first term 2012 - Sevilla Cruz, Ángel Raúl (2012)
Nowadays the English language is important, due that it has been considered the official language of the world; this language can open opportunities for the professional development, for this reason this project presents the implementation of a manual in English inside the Armored Cavalry School, where elite soldiers are trained. This project consists in the creation of a new English procedure manual before, during and after shooting with the AMX-13 Tank of 105mm, this manual will allow teaching English military personnel attending the especialization training course in the Armored Cavalry School, who have a basic knowledge of English language, so they will be able to understand the instruction in a new language. With the creation of this new manual in English, the school will have an excellent instructional aid for teachers or instructors, because they will be able to educate themselves in another language and to teach to the students. In addition, this manual will enable the foreign military personnel who come to take courses in our country; they can get a manual in their own language here in Ecuador and they will be able to understand the lessons taught in this school. Finally, this manual will help military personnel practice the English language with native speakers which will contribute to get higher education that will go hand in hand with new technologies.